Implementasi Regulasi Emosi dalam Meningkatkan Efikasi diri Difabel - Dhian Riskiana Putri (At-Taujih : Bimbingan dan Konseling Islam, 2020)
People with disabilities still experience many difficulties in their social life. People with disabilities rarely get the opportunity to get a good education and job. Some people still consider diffable as people who have shortcomings so that they must be pitied. This social treatment will affect the level of self-efficacy in persons with disabilities. The diffable is expected to be able to increase self-efficacy by controlling emotions skills so that they do not get trapped in pessimistic thinking. Counseling steps with emotional regulation techniques are offered to overcome the problem of self-efficacy with disabilities. This study aims to find the implementation of counseling services with emotion regulation techniques to increase the self-efficacy of people with disabilities. This research is important because people with disabilities need assistance in increasing self-efficacy due to the social treatment they receive. This study uses literature study techniques by looking for reference sources related to disabilities, self-efficacy, and emotion regulation techniques. The library sources are then combined, to then look for the formulations and conclusions.